Assessment of Coral Reef Condition in Nusi Island, Nabire, Indonesia - Nicodemus Rahanra; Abdul Hamid Toha; Paulus Boli; Selvi Tebay (Goodwood, 2026)
Purpose: This study aimed to assess coral reef health at Nusi Island, Nabire, Indonesia, by analyzing the benthic composition using Remotely Operated Vehicle (ROV) technology. Research Methodology: Data were collected using the Underwater Photo Transect (UPT) method, deploying a 50-meter transect line at approximately 10 m depth. High-resolution images were captured, and 1,500 data points were analyzed to evaluate the benthic substrate composition. Results: The findings revealed severe degradation of coral reefs. Site 2 (Pulau Nusi) showed only 3.13% live coral cover, with sand and rubble dominating the substrate. Site 1 (Nabire) fared slightly better, with 6.64% live coral cover, although it still showed significant damage. Conclusions: The coral reefs at both study sites are severely degraded, with Site 2 in a critical state, mainly due to sedimentation. These data highlight the need for targeted management strategies to mitigate these stresses and foster reef recovery. Limitations: This study was limited to a single 50-meter transect at one depth, providing a snapshot of the reef condition. Further research is required to identify specific degradation drivers and conduct long-term monitoring. Contributions: This study provides the first quantitative assessment of coral reef conditions on Nusi Island, offering essential baseline data for future conservation efforts.